Petrography, alteration and genesis of iron mineralization in Roshtkhar - Habib Biabangard; Mohammad Boomeri; Khosro Taimouri; Fatemeh Mohammadpour (Journal of Economic Geology, 2017)
Introduction Iron mineralization in Roshtkhar is located in 48 Km east of the city of Roshtkhar and south of the Khorasan Razavi province. It is geologically located in the north east of the Lut block and the Khaf-Bardeskan volcano-plutonic belt. The Khaf-Bardeskan belt is an important metallogenic province since it is a host of valuable ore deposits such as the Kuh-e-Zar Au-Spicularite, the Tanourcheh and the Khaf Iron ore deposits (Karimpour and Malekzadeh Shafaroudi, 2007). Iron and Copper mineralization in this belt are known as the hydrothermal, skarn and IOCG types (Karimpour and Malekzadeh Shafaroudi, 2007). IOCG deposits are a new type of magmatic to hydrothermal mineralization in the continental crust (Hitzman et al., 1992). Precambrian marble, Lower Paleozoic schist and metavolcanics are the oldest rocks of the area. The younger units are Oligocene conglomerate, shale and sandstone, Miocene marl and Quaternary deposits. Iron oxides and Cu sulfides are associated with igneous rocks. Fe and Cu mineralization in Roshtkhar has been subject of a few studies such as Yousefi Surani (2006). This study describes the petrography of the host rocks, ore paragenesis, alteration types, geochemistry, genesis and other features of the Fe and Cu mineralization in the Roshtkhar iron.